VALIDATION OF AFFORDABLE AND APPLICABLE KIDNEY PHANTOM MODEL (AARM) FOR ULTRASOUND-GUIDED PERCUTANEOUS NEPHROSTOMY SIMULATION - Septian, Regi; Adi, Kuncoro (Indonesian Journal of Urology, 2020)
Objective: Percutaneous nephrostomy (PN) is a medical skill that requires the repetition of hand and eye coordination exercises. The limited opportunity to achieve learning curve at mastering it, increases the morbidity risk to the patient. We therefore developed an Affordable and Applicable Renal Model (AARM) phantom to simulate percutaneous nephrostomy with ultrasound (USG) guiding. Our goal is to present the development of an affordable cost kidney phantom model and evaluate validity (face, content, and construct) with its reliability. Material & Methods: The AARM phantom made from mixture of gelatin, glycerin and sorbitol, then molded with latex gloves comprising the parenchymal portion and the renal pelvicalyceal system connected to a 10Fr nasogastric tube and a 20 cc syringe. Phantom then assessed by urology residents at Hasan Sadikin Hospital Bandung. Senior resident (n=20) who are adept at performing independent PN then compared with junior resident (n=15), and then we analysis both group skills by measure PN initial puncture time and its failure to establish its validity and reliability. Results: This phantom cost production was 30USD (400.000 IDR) and after tested by urology residents, it had simulated the series of PN action steps which described the face and content validation test, with correlation results (Pearson, p<0.05); Very strong (53.8%), strong (30.8%), and medium (15.4%). The reliability test with cronbach alpha value was 0.934 (reliable if cronbach alpha>0.60). The average initial puncture time measure and PN failure result of junior and senior residents are respectively 37.03 ± 9.5 vs 10.90 ± 0.65 seconds and 4.93 ± 1.33 vs 0.75 ± 0.63 times. When both skills performance was analyzed, the senior resident showed significantly (p<0.01) faster and fewer errors. Conclusion: This AARM phantom had successfully represent the whole sequence actions key step of PN skills and this study has been established its validity (face, content and construct). In addition, this phantom material not only made from affordable cost but also applicable and could be used repeatedly (recycled). We propose the use of this AARM phantom simulator as an initial steps practices to introduce percutaneous nephrostomy skills to residents before they went to the operating room.